Peran customer satisfaction sebagai mediator dalam hubungan antara brand experience dan brand loyalty - Lyman, Reyner Alexander; Susan, Marcellia; Istiharini, Istiharini (Jurnal Manajemen Maranatha, 2023)
The development of the smartphone industry has caused market competition between smartphone manufacturers to become increasingly dynamic. Samsung smartphone line currently dominates the global market share. However, from year to year, Samsung market share continues to decline. Apart from that, many consumers complain about experience, loyalty, and satisfaction. The study aims to ascertain how brand experience, which is mediated by customer loyalty to Samsung smartphones, affects customer satisfaction. The research method used is descriptive research with a quantitative approach using the Partial Least Square Structural Equation Model (PLS-SEM). The criteria for this research were 216 respondents aged at least 20 years in Indonesia and using Samsung smartphones. Data collection uses an online questionnaire and non-probability sampling. The findings demonstrate that, through customer satisfaction, brand experience positively impacts customer loyalty.